Sports betting incentives encourage gamblers to select the long odds: An experimental investigation using monetary rewards - Rockloff, Matthew J. (J Behav Addict, 2019)
BACKGROUND AND AIMS: Incentives for wagering products can provide extra value to gamblers. However, there is no financial reason why this added value should lead people to take greater gambling risks. This study aimed to experimentally test if wagering incentives cause gamblers to choose higher-risk (long odds) bets than un-incentivized bets. METHODS: An online experiment was conducted with wagering customers (N = 299, female = 12). Participants bet $4 on each of six video game simulations of a sport that they had wagered on in the past 12 months (Australian Football League, Cricket, or Soccer). Each game offered different common wagering incentives: Bonus bet, Better odds/winnings, Reduced risk, Cash rebate, Player’s choice of inducement, or No-inducement. For each game, participants could bet on long, medium, or short odds, and subsequently viewed a highlight reel of the simulated game outcome and bet outcome. RESULTS: Participants selected significantly longer odds (i.e., riskier) bets on games when an incentive was offered compared to the No-inducement condition. Better odds/winnings was the most attractive incentive, followed by Bonus bet, Cash rebate, Reduced risk, and No-incentive, respectively. No significant differences were observed based on demographics or problem gambling severity. DISCUSSION AND CONCLUSIONS: The choice of long odds with incentivized bets increases the volatility of player returns. Increased volatility results in more gamblers in a losing position and fewer gamblers with larger wins. Moreover, if long odds bets are priced to provide poorer value to bettors compared to short odds, they would increase gamblers’ losses and equivalently increase operators’ profits.